Critical GIS as a tool for social transformation - Pavlovskaya, Marianna (The Canadian geographer, 2018)
When Critical GIS emerged in the 1990s and gained momentum in the 2000s, its potential for enabling progressive social change generated considerable excitement. By combining the powers of mapping, information technologies, and critical social theory, it promised new possibilities for acting upon the growing social contradictions of the neoliberal era. Critical GIS seemed to open a pragmatic plane of action by fusing progressive geographic imaginations with concrete and tangible maps. As I reflect on the state of critical GIS in the middle of the second decade of the 21st century, new configurations of class power, patriarchy, and racism are rapidly reshaping our social and geopolitical worlds and are precipitating environmental destruction. Yet, I attempt to develop the idea that GIS is a tool for social transformation because it can produce new cartographies and spaces of possibility and build and expand geographies of hope and care that change social imaginaries in favour of non‐hierarchical class, gender, and race relations. In short, critical GIS scholarship both engages ongoing progressive politics and can create new possibilities for change. In particular, I examine two interventions of critical GIS: creating cartographies of solidarity and teaching. La science de l'information géographique critique comme outil de transformation sociale Lorsque la science de l'information géographique critique est apparue durant les années 1990 et a gagné en popularité au cours des années 2000, son potentiel pour un changement social progressif a suscité un enthousiasme considérable. En combinant les potentiels de la cartographie, des technologies de l'information et de la théorie sociale critique, elle a ouvert de nouvelles possibilités de tirer parti des contradictions sociales croissantes de l’ère néolibérale. Elle a semblé ouvrir un plan d'action pragmatique en fusionnant des vues géographiques progressives avec des cartes concrètes et tangibles. Alors que je réfléchis à l’état de la science de l'information géographique critique au milieu de la deuxième décennie du 21e siècle, de nouvelles configurations du pouvoir des classes, du patriarcat et du racisme redéfinissent rapidement notre monde géopolitique et social et précipitent le déclin environnemental. Pourtant, je tente de développer l'idée que les SIG sont un outil de transformation sociale parce qu'il peut produire de nouvelles cartographies et de nouveaux espaces de possibilités et bâtir et étendre des géographies de l'espoir et de la bienveillance qui changent l'imaginaire social au profit de relations de classes, de genres et de races non hiérarchiques. Bref, le cursus d’études en science de l'information géographique critique implique des politiques progressistes et peut également créer de nouvelles possibilités pour le changement. J'ai examiné plus particulièrement deux interventions : la création de cartographies de solidarité et pédagogiques. Key Messages Critical GIS opens a pragmatic plane of action by fusing progressive geographic imaginations with concrete and tangible maps. GIS can produce new cartographies of spaces of possibility from which geographies of hope and care can expand. Critical GIS scholarship can contribute to social transformation by, for example, creating cartographies of solidarity economy and being part of critical pedagogy.